Webcam camera as a detector for a simple lab-on-chip time based approach - Wasin Wongwilai (2018)
A modification of a webcam camera for use as a small and low cost detector was demonstrated with a simple lab-on-chip reactor. Real time continuous monitoring of the reaction zone could be done. Acid-base neutralization with phenolphthalein indicator was used as a model reaction. The fading of pink color of the indicator when the acidic solution diffused into the basic solution zone was recorded as the change of red, blue and green colors (%RBG.) The change was related to acid concentration. A low cost portable semi-automation analysis system was achieved. © 2010 Elsevier B.V. All rights reserved.